Characteristics of Coherent Photon Transport in Semiconductor Waveguide Cavity System (Bulletin of Pure and Applied Sciences – Physics, 2022)
We have studied the characteristic feature of coherent photon transport in a semiconductor  waveguide. We have presented a semiconductor master equation formalism that accurately  simulated coherent input or output coupling of semiconductor cavity quantum  electrodynamics systems such as planar photonic crystals and micropillar cavities. The role of  quantized multiphoton effects pointed out the possible failure of weak excitation  approximation, which was found to fail even for low input powers and small mean cavity  photon numbers. For increasing field strengths, possible failure of the semiclassical approach  was taken into account. In the weak coupling regime, higher order quantum correlation  effects, were shown to be significant. We have introduced the general theoretical technique to  simulate coherent photon transport outside both the weak excitation approximation and the  semi classical approximation. Electron-phonon interactions at a microscopic level were  derived using polaron transformation. We have demonstrated that substantial deviations  from the weak excitation approximation resulted for very small mean photon numbers. We  have modified the master equation approach to include the mechanism of electron-acoustic  scattering and studied the impact of electron-phonon interaction on incoherent scattering and  coherent renormalization of the exciton cavity coupling rate, qualitative differences from  simple Lorentzian decay model containing quantum dot were found. We have also studied  the transmission of light in the strong coupling regime and simulated a phase gate. We have  found that coupling to an acoustic phonon bath caused considerable qualitative changes in  light propagation characteristics modeled by a simple pure dephasing process. We have used  the model to simulate a conditional phasegate. The obtained results were found in good  agreement with previously obtained results.